Dekonstruksi Karakter Miranda dalam Novel Picnic at Hanging Rock Karya Joan Lindsay - Ahmad, Hafidh Dwi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2025)
This article examines the character of Miranda in Joan Lindsay’s novel Picnic at Hanging Rock through the lens of Jacques Derrida’s deconstruction. Miranda, initially portrayed as the ideal figure, beautiful, calm, gentle, and compassionate, reveals a deeper complexity that is not explicitly articulated in the narrative. By applying Derrida’s concepts of différance and the metaphysics of presence, this article deconstructs the way the text constructs a meaning of Miranda that is never stable. She emerges as a symbol of meaning in constant deferral and slippage, never fully present as a subject. The analysis reveals that the idealization of Miranda ultimately obscures her existence as an individual, rendering her more as a trace of cultural and colonial constructs. Thus, the article argues that Miranda’s presence in the text is a form of absence itself a representation that always eludes complete meaning.